(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to examine the role of agricultural biotechnology in improving the productivity, quality, and resilience of food crops as an effort to support sustainable agriculture. The method used is a systematic literature review of relevant national and international journal articles published between 2014 and 2025. The literature was analysed descriptively by grouping the findings based on aspects of increased productivity, crop quality, and crop resistance to biotic and abiotic stresses. The results of the analysis show that the application of biotechnology, such as genetic engineering through CRISPR-Cas9 and Agrobacterium transformation, tissue culture, and the use of functional microorganisms such as PGPR and mycorrhiza, has been proven to increase crop yields, improve nutritional content through biofortification, and increase crop resistance to pests, diseases, and environmental stress. These findings confirm that biotechnology has a significant contribution in producing superior plant varieties that are more adaptive and environmentally friendly. Thus, the integration of biotechnology into agricultural systems has the potential to become an important strategy in supporting food security and sustainable agricultural development.